STRATEGI MANAJEMEN KONTEMPORER DAN KEPEMPINAN DIGITAL DI ERA AI - Tabroni; Albilal, Ikram; Setya Arwidya, Meita; Mahfuzah; Suswanti, Lusi; Azkia, Muna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) has driven transformation in various aspects of educational management, including in madrasahs. The use of AI in administration, learning evaluation, data management, and decision-making offers opportunities to improve the effectiveness and efficiency of educational institution management. However, the application of this technology also poses challenges in maintaining the moral, ethical, and character values ​​that are characteristic of Islamic education. This study aims to analyze contemporary management strategies and the digital leadership of madrasah principals in integrating AI technology without neglecting the moral development of students. The method used is library research by reviewing various scientific literature, books, journals, and documents related to educational management, digital leadership, and the implementation of AI in Islamic education. The results of the study indicate that madrasah principals have a strategic role in directing digital transformation through strengthening digital literacy, utilizing AI for administration and learning assessment, developing teacher competencies, and formulating technology use policies based on Islamic values. Effective digital leadership is not only oriented towards technological innovation, but also on establishing an organizational culture that upholds ethics, responsibility, and good morals. The novelty of this research lies in its study of the integration of AI into madrasah management and leadership, which focuses not only on the technical aspects of technology use but also on efforts to maintain and strengthen Islamic moral values ​​during the digital transformation process. Therefore, contemporary management strategies and values-based digital leadership are key to realizing madrasahs that are adaptive to technological developments while maintaining their Islamic identity.